Hypertriglyceridemia associated with insulin resistance in children with obesity: Hipertrigliceridemia asociada a resistencia a la insulina en niños con obesidad - Cacha Villacorta, Rosario Patricia (2024)
Introduction: Hypertriglyceridemia has been linked to insulin resistance.Objectives: To evaluate the relationship and predictive capacity of hypertriglyceridemia for insulin resistance in obese children.Methods: A cross-sectional analytical study was conducted in obese children aged 6 to 14 years, treated at the Belén Hospital of Trujillo between 2014 and 2019. Fifty-eight randomly selected medical records were analyzed. Insulin resistance was measured using the Homeostasis Model Assessment (HOMA) index (≥3). Descriptive, correlational analyses, and Odds Ratio (OR) calculations were used, along with predictive indicators such as sensitivity and specificity.Results: Of the 58 children studied, 58.6% had elevated triglyceride levels and 74.1% showed insulin resistance. There was a significant correlation between triglyceride levels and the HOMA index (coef.: 0.543; p<0.001). Elevated triglyceride levels (OR=18.91; 95% CI: 3.67-97.36; p<0.001), fasting glucose (OR=46.20; 95% CI: 5.39-396.06; p=0.010), fasting insulin (OR=52.89; 95% CI: 6.11-457.55; p<0.001), and the presence of acanthosis nigricans (OR=36.17; 95% CI: 4.28-305.98; p<0.001) were significantly associated with insulin resistance. Hypertriglyceridemia showed a sensitivity of 74.4% and a specificity of 86.7% for predicting insulin resistance.Conclusion: Hypertriglyceridemia is significantly associated with insulin resistance in obese children and has an acceptable performance as a predictor. This factor may serve as an early marker and predictor to implement appropriate preventive measures in vulnerable populations.